Digital Government in Social Sciences Discipline: Mapping Pivotal Features and Proposed Theoretical Model - Hasanah, Siti; Pratama, Inka Nusamuda; Rahmat, Al Fauzi; Kurniawan, Cahyadi (SCAD Independent, 2023)
The research aimed to describe the trend issues, identify the key features, and propose a theoretical model of digital government. A comprehensive search was used to find eligible articles in the Academic Scopus Database. Further, the quality of the study was assessed during the screening phase, where it met 115 journal-related articles on digital government within the social sciences discipline. Further, this literature was analyzed by NVivo 12 Plus via a hierarchy diagram, cluster analysis, word frequency analysis, and the VOSViwer tool to visualize the data via a network, overlay, and density analysis. The findings revealed a term network formed by digital government and trend issues, resulting in several growing concerns, such as e-government, open government, and technology adoption. Furthermore, key features were reported following proportional analysis, such as systems, development, services, models, information, public, policy, management, and networks. Another point is that a proposed theoretical model has been constructed and selected for future research.